The risk of pathogenic intestinal parasitic infections in vegetables and vegetables handlers in some of Baghdad markets - Rawaa A. Hussein Al-jeboori (مجلة كلية الطب, 2011)
Back ground: Intestinal parasitic infections are among the most common infections world wide and are regarded as a serious public-health problem. Methods: The study was carried out during the period from October 2008 to the end of January 2009 in five different markets of Baghdad. Six different type of vegetables were selected for this study including tomato, onion, cabbage, lettuce, carrot and pepper. The vegetables soaked for 10 minutes and washed in saline, centrifuged and the sediment examined for the presence of intestinal parasites. A total of 168 specimens of faeces were collected from vegetables handlers of the markets studied then, specimens were examined for the presence of intestinal parasites by the direct smear method and the concentration method. Results: Entamoeba histolytica cysts and ova of Ascaris lumbricoides isolated from all types of vegetables studied except onion. Giardia lamblia cysts found on cabbage and lettuce. Ova of Enterobius vermicularis and Hymenolepis nana were isolated from tomato, cabbage and lettuce. In addition, the ova of Trichuris trichiura and Taenia spp. were isolated from cabbage and lettuce. Also about third of the vegetables handlers surveyed (36.3%) were infected with one or more of intestinal parasites. Entamoeba histolytica was the commonest intestinal protozoan detected, with a prevalence rate of (31.1%), followed by Giardia lamblia (14.8%). Ascaris lumbricoides and Hymenolepis nana were the most common helminths detected with a prevalence rate of 19.7% and 13.1% respectively, with no significant difference between both sexes of the people examined. Conclusion: The vegetables and vegetables handlers may play an important role in the prevalence of intestinal parasitic infections.